Pembinaan Akhlak Siswa melalui Integrasi Pesantren dan Sekolah (Studi Analisis di SMK Ma’arif 1 Kebumen) - Mugiarto Mugiarto (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2020)
The role of Islamic boarding schools in fostering morals is undeniable with the many challenges and trials for students' lives. This study aims to describe and find out about the role of Islamic boarding schools in fostering youth association at SMK Ma'arif 1 Kebumen. This research is a field research and a type of qualitative research. Data collection techniques using observation, documentation and interviews. The data analysis technique used is descriptive qualitative analysis which consists of 3 activities that take place simultaneously, namely data reduction, data presentation and drawing conclusions. This technique is used as a reference for writing research results and makes it easier to understand the description presented by the final research results. The research will look for the role of Islamic boarding schools in developing morals at SMK Ma'arif 1 Kebumen. It is hoped that from coaching youth as the next generation of the nation, they can give birth to a good generation. A generation that is able to maintain noble values ​​but can contribute to the development of the Indonesian nation both physically and spiritually.